Daphnetin ameliorates experimental colitis by modulating microbiota composition and Treg/Th17 balance. Issue 8 (30th May 2019) - Ji, Jianjian; Ge, Xiaoyin; Chen, Yugen; Zhu, Bo; Wu, Qinan; Zhang, Junfeng; Shan, Jinjun; Cheng, Haibo; Shi, Liyun
ABSTRACT: Inflammatory bowel diseases (IBDs) are characterized by chronic pathologies associated with extensive gut dysbiosis and intestinal inflammation. Hence, endeavors to improve the inflammatory pathology by manipulating gut microbiota are ongoing. Daphnetin (DAPH) is a coumarin derivative extracted from Daphne odora var with anti‐inflammatory and immune‐regulatory properties that has been widely used in treating inflammatory disorders. Herein, we showed that DAPH remarkably alleviated experimental colitis by reducing colonic inflammation, improving colonic integrity, and reestablishing immune and metabolic homeostasis in the inflicted intestines. Our analysis showed that DAPH modified the composition of gut microbiota and altered the metabolic profiles in dextran sulfate sodium–treated mice. In particular, this agent significantly elevated the abundance of short‐chain fatty acid (SCFA)–producing gut microbiota, causatively related with the enhanced development of Treg cells and the reduced proinflammatory Th 17 cell differentiation. More critically, the protective effect of DAPH was shown to be transmissible among colitic mice through cohousing or fecal microbiota transplantation, further substantiating the importance of SCFA‐producing gut microbiota in DAPH action. We thus for the first time reveal the potential of DAPH in resetting the gut microbiome and reestablishing immune homeostasis in colitic mice, which may have clinical implications for treating IBD.—Ji, J., Ge, X., Chen, Y., Zhu, B., Wu, Q., Zhang, J., Shan, J., Cheng, H., Shi, L. Daphnetin ameliorates experimental colitis by modulating microbiota composition and Treg /Th 17 balance. FASEB J. 33, 9308–9322 (2019). www.fasebj.org